Metastatic breast cancer survival improvement restricted by regional disparity: Surveillance, Epidemiology, and End Results and institutional analysis: 1990 to 2011 - Malmgren, Judith A. (Cancer, 2019)
BACKGROUND: The extent of breast cancer outcome disparity can be measured by comparing Surveillance, Epidemiology, and End Results (SEER) breast cancer‐specific survival (BCSS) by region and with institutional cohort (IC) rates. METHODS: Patients who were diagnosed with a first primary, de novo, stage IV breast cancer at ages 25 to 84 years from 1990 to 2011 were studied. The change in 5‐year BCSS over time from 1990 to 2011 was compared using the SEER 9 registries (SEER 9) without the Seattle‐Puget Sound (S‐PS) region (n = 12,121), the S‐PS region alone (n = 1931), and the S‐PS region IC (n = 261). The IC BCSS endpoint was breast cancer death confirmed from chart and/or death certificate and cause‐specific survival for SEER registries. BCSS was estimated using the Kaplan‐Meier method. Hazard ratios (HzR) were calculated using Cox proportional‐hazards models. RESULTS: For SEER 9 without the S‐PS region, 5‐year BCSS improved 7% (from 19% to 26%) over time, it improved 14% for the S‐PS region (21% to 35%), and it improved 27% for the S‐PS IC (29% to 56%). In the IC Cox proportional‐hazards model, recent diagnosis year, chemotherapy, surgery, and age <70 years were associated with better survival. For SEER 9, additional significant factors were white race and positive hormone receptor status and S‐PS region was associated with better survival (HzR, 0.87; 95% CI, 0.84‐0.90). In an adjusted model, hazard of BC death decreased in the most recent time period (2005‐2011) by 28% in SEER 9 without S‐PS, 43% in the S‐PS region and 45% in the IC (HzR, 0.72 [95% CI, 0.67‐0.76], 0.57 [95% CI, 0.49‐0.66], and 0.55 [95% CI, 0.39‐0.78], respectively). CONCLUSIONS: Over 2 decades, the survival of patients with metastatic breast cancer improved nationally, but with regional survival disparity and differential improvement. To achieve equitable outcomes, access and treatment approaches will need to be identified and adopted.